L’enseignement à Bruxelles - Rudi Janssens; Donat Carlier; Piet Van de Craen (Brussels Studies)
This paper focuses on the situation of compulsory education in the Brussels Capital Region. Schools are not isolated entities within which the learning process takes place and can not be viewed separately from the metropolitan environment within which they function. In order to gain an insight into this complex issue, the relationship between both can be summarised by four aspects: the political-institutional context (the organisation of education), the pedagogical-educational process (what is taught and how, in what circumstances and with which expected result), the demographic-geographic situation (the population for whom education is organised), and the social-cultural context (urban development) (Verlot, 2002). Although these different aspects are strongly interwoven, this division provides an interesting means by which the actual situation in Brussels is looked at more closely and by which the observations and the formulation of problems are made clearer. Finally, a number of political options are proposed.Due to the extent of the problems, the higher education and vocational education sectors are not examined here. They are addressed within topics such as “Brussels as a city of knowledge” and “The Brussels employment market”.